Pengaruh Efikasi Diri dan Model Pembelajaran CTL Terhadap Minat Belajar PAK dan Budi Pekerti Siswa Kelas IX SMP Negeri 1 Badiri - Debora Sitohang (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2025)
This study aims to analyze: 1) the effect of self-efficacy on the interest in learning PAK and Budi Pekerti of students in grade IX SMP Negeri 1 Badiri; 2) the effect of CTL learning model on the interest in learning PAK and Budi Pekerti of students in grade IX SMP Negeri 1 Badiri; 3) the effect of self-efficacy and CTL learning model together on the interest in learning PAK and Budi Pekerti of students in grade IX SMP Negeri 1 Badiri. The method used in this research is quantitative research method with explanatory approach. The population of ninth grade students of SMP Negeri 1 Badiri in the 2024/2025 academic year was 136 people and 25% of the population became the sample in this study, namely 34 people. Data were collected using a closed questionnaire of 50 items. The results of data analysis show that: 1) there is a positive and significant effect of self-efficacy on interest in learning PAK by 18.3%; 2) there is a positive and significant effect of CTL learning model on interest in learning PAK by 24%; and 3) there is a positive and significant effect of self-efficacy and CTL learning model together on interest in learning PAK by 27.4%.